Optimasi Peran Aktif Masyarakat dalam Upaya Pencegahan dan Penanggulangan COVID-19 serta Pemberdayaan Ekonomi bagi Penduduk di Desa Dilib Lamteungoh, Kecamatan Sukamakmur, Aceh Besar - Azwar, Azwar; Mukhlishien, Mukhlishien; Abubakar, Abubakar; Hasrina, Cut Delsie; Mulana, Farid (Universitas Syiah Kuala, 2023)
The rapid spread of COVID-19 has had a significant impact on people's lives. Apart from having an impact on health, COVID-19 also affects the economic aspects of society. Therefore, various parties, including academics in tertiary institutions, participate in efforts to mitigate these impacts. One form of academic participation is through the Community Service Program, which provides counseling related to COVID-19. Universities have an important role in preventing and controlling the spread of COVID-19. To anticipate greater effects and risks, the academic community, especially teaching staff at the Syiah Kuala University, needs to intervene directly to assist the government and the community in preventing and controlling COVID-19. Educational activities on prevention and control of COVID-19 for community members in Dilib Lamteungoh Village, Sukamakmur District, Aceh Besar, are part of the implementation of the Tri Dharma of Higher Education, namely Community Service. The main focus of this community service activity is to provide basic knowledge to the public about the importance of caution in preventing the threat of COVID-19, as well as increase community preparedness and response in preventing the spread of Corona Virus Disease-19. In this community service, our main focus is to provide education about the prevention and control of COVID-19 for local community members. After counseling, it is hoped that community members will have a better understanding of handling COVID-19.